Mother’s Coping strategies toward Food Insecurity during COVID-19 Pandemic: A Review Article - Sherly Ardi Vantono; Luh Ade Ari Wiradnyani; Saptawati Bardosono (Indonesian Nutrition Association, 2022)
The COVID-19 pandemic has impacted many aspects of the country, including the economy and health care. Food insecurity is increasing, causing harm to children’s nutrition and development. As a result, mother must deal with food insecurity to providing a balanced diet for her children aged 6 to 23 months. This study aims to review the possible mother’s coping strategies used toward food insecurity to maintain child nutrition during the COVID-19 pandemic. To review the literature, the researcher utilized search engine such as PubMed, ScienceDirect, Oxford journal, and British Medical Journal.